The issues of torture and execution during the Algerian revolution: Djamila Boupacha a model - daachi, samira (The Algerian Historical Journal, 2026)
The fighter Djamila Boupacha is one of the symbols of the Algerian national resistance, during the revolution, they assigned her several tasks, including carrying out commando operations in the heart of the Algerian capital, a nurse, helping the Mujahedeen with medicines, …etc. When they arrested her, she was subjected to all forms of illegal torture before appearing in court, and creating a file full of fake facts for the purpose of guillotine punishment. But a helping hand extends to her form Paris, her case was presented to the. She was transferred to the French courts, and she was acquitted after many questions and representative scenes in order to reach realistic facts about this complex case.